1996
DOI: 10.1097/00003246-199609000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Surface heparinization of central venous catheters reduces microbial colonization in vitro and in vivo

Abstract: Covalent end point surface heparinization appears to have a great impact on both in vitro and in vivo bacterial colonization of central venous catheters. Such heparinization can be a practical and economical approach to the prevention of catheter-associated bacteremia or fungemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(67 citation statements)
references
References 32 publications
0
66
0
1
Order By: Relevance
“…[12][13][14] There are many hypotheses about how heparin reduces bacterial adhesion; in an environment with a low protein content such as urinary tract, the effect of heparin could result from its hydrophobicity and negative charge. 14 Ruggieri and associates 14 showed a 90% reduction of bacterial adhesion on heparin-coated catheter surfaces, while Hildebrandt and colleagues 13 demonstrated reductions in stent encrustation by heparin coating in another study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] There are many hypotheses about how heparin reduces bacterial adhesion; in an environment with a low protein content such as urinary tract, the effect of heparin could result from its hydrophobicity and negative charge. 14 Ruggieri and associates 14 showed a 90% reduction of bacterial adhesion on heparin-coated catheter surfaces, while Hildebrandt and colleagues 13 demonstrated reductions in stent encrustation by heparin coating in another study.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] Heparin coating was proposed to prevent bacterial adhesion over the last three decades, especially in vascular medicine. [12][13][14] Heparin is an anticoagulant that carries a strong negative electrical charge and helps prevent cell adhesion. For this reason, heparinization can be a practical and low-cost approach to the prevention of catheter-associated bacteremia or fungemia.…”
Section: Introduction Umentioning
confidence: 99%
“…Reason for exclusion Geffers, 2003 102 Review of the methodological quality of the trials available in this area of research Mermel, 2000 103 All CRBSI preventive strategies Zurcher, 2004 106 Compared single and multilumen CVCs Saint, 2000 40 Clinical and economic consequences of nosocomial CVC-related infection Bambauer, 2004 101 Narrative overview Raad, 1999 104 Narrative overview Sherertz, 2004 105 Narrative overview 3 Maki, 1988 75 Cuff vs non-cuffed ✓ ✓ Flowers, 1989 108 Cuff vs non-cuffed ✓ ✓ Kamal, 1991 109 In-house preparation ✓ ✓ ✓ of AI-CVCs Groeger, 1993 110 Cuff vs 2nd cuff ✓ ✓ Babycos, 1993 72 ✓ Bach, 1994 98 Interim results ✓ ✓ Ramsay, 1994 99 Interim results ✓ ✓ Dahlberg, 1995 111 Silver cuff vs non-cuffed ✓ Goldschmidt, 1995 112 German ✓ ✓ ✓ Smith, 1995 113 Cuff vs non-cuffed ✓ ✓ Trazzera, 1995 114 Non-RCT ✓ ✓ Appelgren, 1996 115 Standard CVC vs ✓ heparin-bonded CVC Bach, 1996 53 In-house preparation ✓ ✓ of AI-CVCs reviewed. Below are some of the issues that were raised by the reviews.…”
Section: Appendixmentioning
confidence: 99%
“…The intraluminal thrombus acts as a nidus for the catheter biofilm, and in vitro studies have shown decreased adherence of bacteria to heparin-coated catheters compared with noncoated catheters (5). Moreover, two randomized clinical trials in hospitalized patients with short-term, nontunneled central vein catheters found a lower risk of catheter-related bacteremia in patients with heparincoated catheters (5,6).…”
mentioning
confidence: 99%